Energy and economic analysis of building integrated with PCM in different cities of China. (1st August 2016) - Mi, Xuming; Liu, Ran; Cui, Hongzhi; Memon, Shazim Ali; Xing, Feng; Lo, Yiu
Highlights: Performance of PCM office building in five cities of China was evaluated. Energy saving potential of Shenyang was found to be the best. The dynamic payback period was employed for energy economic analysis. PCM investment appears to be attractive in Shenyang, Zhengzhou and Changsha. PCM investment in Kunming and Hong Kong do not offer economic benefits. Abstract: In this research, the effect of phase change material (PCM) on energy consumption of a typical multistory office building located in five different cities (Shenyang, Zhengzhou, Changsha, Kunming and Hong Kong) representing different climate regions of China, was simulated for a whole year using EnergyPlus. Based on the simulation results, the energy savings resulting from PCM application were evaluated. For economic analysis, the static payback period (SPP) and dynamic payback period (DPP), considering different discount rates, were used to assess the application of PCM in a typical official building. Test results showed that the energy savings resulting from PCM application are more prominent for office building located in cold region such as Shenyang and Zhengzhou as well as in hot summer and cold winter (Changsha). From economic analysis, the application of PCM in Shenyang, Zhengzhou and Changsha showed high economic value and the investment appeared to be attractive. However, at current prices, the PCM investment in Kunming and Hong Kong cannot be recovered and do not offer economic benefits.